1979
DOI: 10.1177/014616727900500222
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Attractiveness as a Function of Active vs Passive Support for the Feminist Movement

Abstract: In contrast to earlier studies samples of both males and females selected more attractive photographs as being of supporters of the Feminist Movement and less attractive photos as being of non-supporters. This related to subjects' attitudes toward women but did not interact with the perception of activism within the movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Data using a direct measure of subjects' perceptions of attractiveness add validity to the findings of earlier work (Beaman & Ullrich, 1978;Johnson et al, 1978Johnson et al, , 1979Klentz, et al, 1983;Unger et al, 1982) showing either no differences or results favouring supporters of the movement. Not all previous research has found significant correlations between the raters' attitudes and the attractiveness ratings of the photos.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Data using a direct measure of subjects' perceptions of attractiveness add validity to the findings of earlier work (Beaman & Ullrich, 1978;Johnson et al, 1978Johnson et al, , 1979Klentz, et al, 1983;Unger et al, 1982) showing either no differences or results favouring supporters of the movement. Not all previous research has found significant correlations between the raters' attitudes and the attractiveness ratings of the photos.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the attitude measures used have often tapped broad issues concerning the role of women in society instead of the more focused issue of the women's movement itself; hence, correlations in these cases would be expected to be attenuated compared to those that may be obtained with more specific measures (Azjen & Fishbein, 1980). However, significant correlations between .20 and .49 have been reported (Johnson et al, 1978(Johnson et al, , 1979Klentz et al, 1983) supporting the attitude similarity mediation explanation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nonetheless, there have been no reports of individual differences in this tendency. Even attempts at correlating attractiveness stereotyping with attitudes toward the stereotyped groups have met with mixed results (Beaman, Klentz & Conrad, 1984; Dew, in press; Goldberg, Gottesdiener & Abramson, 1975; Johnson, Holborn & Turcotte, 1979).…”
mentioning
confidence: 99%